Reflections on pedagogical paradigms in design - Esquivel, Luz del Carmen Vilchis (Seven Editora, 2023)
Education is a consubstantial process of human nature. Since the most remote Paleolithic there has been intentionality, in the course of many generations, efforts have been made to assimilate culture to the environment, developing new skills and domains. The diffuse and incidental education that occurred in the family environment, in communities or small societies, was transformed into a specialized function of society, which gradually shaped the school institution. The school, which at first was a place specialized in the learning of literate culture, sacred culture and elites, gradually gave way in the twentieth century to a place of generalized and compulsory attendance in those populations with advanced technology. Thus, school is an essential condition for any citizen to survive and adapt to the environment.In this passage to formal education, multiple disciplines were historically inserted, among which design stands out for its "schooled youth". The place that design currently holds in education has meant a process of progressive generalization of its teaching modalities and the way to achieve it. In many of the reflections that have been carried out to support the schooling of design, there are important psychological, pedagogical and philosophical considerations.It is relevant to understand, on the one hand, the pedagogical references, shared by educational psychology to interpret the philosophical ones, since the former provide the elements to observe the student, the learning process and the learning situation, and the latter are the support that argues and validates each of these domains. DOI:https://doi.org/10.56238/sevened2023.006-069